Pengaruh Pemanfaatan Media Pembelajaran Zoom Meeting Terhadap Hasil Belajar Peserta Didik di SMA Negeri 4 Bekasi - Amri Dunan; Arman (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to determine the effect of using zoom meeting learning media on student learning outcomes in the Informatics subject class X. The research method used is quantitative method, with data analysis using simple correlation techniques and regression analysis. The results showed a significance value of 0.003 <0.05, meaning that there was a relationship and the Person Correlation was 0.326, the value of r Square of 0.107 means 10.7% of the dependent variable, the value of t count is 3.049 > 2.00 with a significance of 0.003 < 0.05 meaning H0 is rejected and H1 is accepted, so that it can be seen that there is an effect of using zoom meeting learning media on the learning outcomes of class X students in informatics subjects.